Factors influencing the green purchase behaviour of millennials: An emerging country perspective - Nombulelo Dilotsotlhe (Cogent Business & Management, 2021)
The study investigates the determinants of green purchase behaviour amongst the millennial cohort in an emerging market of South Africa. The research was theoretically grounded on the diffusion of innovation and the theory of planned behaviour models. A descriptive quantitative research design was followed and primary data was gathered using a self-administered questionnaire. A total of 355 complete responses were suitable for analysis. A partial least squares structural equation modelling technique was used to determine the significance of the interrelationships between the items measuring the study's constructs. Furthermore, the measurement and structural models were assessed. The findings concluded that all the significant independent variables (relative advantage, compatibility and observability) explained 84.0% of the variance in attitude towards green purchase behaviour. Attitudes, subjective norm and perceived behavioural control explained 83.4% of the variance in behavioural intention towards green purchase behaviour and behavioural intention explained 24.2% of the variance in adoption behaviour. It is therefore important for the green industry of South Africa to cultivate the adoption behaviours of green products towards their customer base, thereby securing the further growth of this niche market segment and enhancing purchase behaviours in the long run.
Keywords: 650; Green purchase behaviour; millennials; attitudes; behavioural intention; perceived behavioural control; adoption behaviour